2022
DOI: 10.1111/aos.15229
|View full text |Cite
|
Sign up to set email alerts
|

Corneal transplantation in aniridia‐related keratopathy with a two‐year follow‐up period, an uncommon disease with precarious course

Abstract: Aniridia-related keratopathy (ARK) is a sightthreatening, painful, chronic progressive keratopathy present in aniridia, a congenital autosomal dominant disease caused by haploinsufficiency of the Pax6 transcription factor (Lee et al., 2008). ARK is characterized by the presence of a disturbed limbal stem cell niche, altered corneal epithelial differentiation pathways

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…For example, A. Viberg et al performed corneal limbal stem cell transplantation, L. C. Van der Wekken-Pas et al also conducted a study on the treatment of Candida keratitis and endophthalmitis after corneal transplantation, and S. Obata et al performed antivascular endothelial growth factor therapy and laser therapy for Retinopathy of Prematurity. However, physical assistance as well as pharmacologic surgical treatment can only slow down the progression of ocular lesions and do not accomplish complete repair of the visual senses [1][2][3]. Visual Prosthesis is an implantable medical electronic device that is currently the most promising technical means to assist patients with visual impairment or severe blindness in restoring visual function [4].…”
Section: Introductionmentioning
confidence: 99%
“…For example, A. Viberg et al performed corneal limbal stem cell transplantation, L. C. Van der Wekken-Pas et al also conducted a study on the treatment of Candida keratitis and endophthalmitis after corneal transplantation, and S. Obata et al performed antivascular endothelial growth factor therapy and laser therapy for Retinopathy of Prematurity. However, physical assistance as well as pharmacologic surgical treatment can only slow down the progression of ocular lesions and do not accomplish complete repair of the visual senses [1][2][3]. Visual Prosthesis is an implantable medical electronic device that is currently the most promising technical means to assist patients with visual impairment or severe blindness in restoring visual function [4].…”
Section: Introductionmentioning
confidence: 99%
“…In some cases, pannectomy with amniotic membrane transplantation as a patch or penetrating keratoplasty is performed or penetrating keratoplasty in a combination with limbal stem cell transplantation. 4,5 The study of Viberg et al 6 showed recurring visual impairment in approximately 60% of patients with AAK 2 years after surgery. Patients can develop AAK at a young age.…”
mentioning
confidence: 99%